2016
DOI: 10.1002/tox.22252
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal exposure to ethinylestradiol promotes different effects on the morphology of the prostate of the male and female gerbil during aging

Abstract: In rodents, the final growth and maturation of the prostate occur at puberty, a crucial period for prostate development. The present study is a serological, morphological, morphometric, and immunohistochemical analysis of the effects of exposure to ethinylestradiol (EE) (15 µg/kg/day) during puberty (EE/PUB group) on the male ventral and female prostate in senile gerbils. In the study, male and female gerbils (Meriones unguiculatus) (42 days) received by gavage 15 μg/kg/day of EE (a component of the contracept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…Indeed, these aspects should be considered nowadays, mainly because we are more exposed to exogenous substances, such as endocrine‐disrupting chemicals (EDCs), that may disrupt and predispose the gland to the development of diseases with aging (Biancardi et al, ; Perez et al, ). A wealth of experimental analyses from our research group employing gerbils has shown that the female prostate is very sensitive to exogenous hormonal interference (Santos et al, ; Biancardi et al, , ; de Lima et al, ; Rodríguez et al, ; Perez et al, ). These studies have shown that the early exposure to exogenous substances, as specific hormones, for instance, increases the susceptibility to the development of prostatic lesions during aging in both male and female gerbils (Biancardi et al, , ; Perez et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these aspects should be considered nowadays, mainly because we are more exposed to exogenous substances, such as endocrine‐disrupting chemicals (EDCs), that may disrupt and predispose the gland to the development of diseases with aging (Biancardi et al, ; Perez et al, ). A wealth of experimental analyses from our research group employing gerbils has shown that the female prostate is very sensitive to exogenous hormonal interference (Santos et al, ; Biancardi et al, , ; de Lima et al, ; Rodríguez et al, ; Perez et al, ). These studies have shown that the early exposure to exogenous substances, as specific hormones, for instance, increases the susceptibility to the development of prostatic lesions during aging in both male and female gerbils (Biancardi et al, , ; Perez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS), adrenal hyperplasia, or even the intake of exogenous hormones may change the glandular homeostasis, disrupting, and threatening the female prostate health. Indeed, the increased use of oral contraceptives has been related with an enhanced susceptibility to the development of prostatic diseases during aging (Perez et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, females showed additional types of tissue disorders such as intraepithelial neoplasia, and stromal inflammatory foci. This type of tissue injuries was also found in the prostate of gerbils exposed to EDCs and to other forms of hormonal manipulation . Epithelial hyperplastic growth, neoplasia, and inflammation are typical events stimulated by chemicals with estrogenic action .…”
Section: Discussionmentioning
confidence: 62%
“…This gland, which was classically described as a male‐exclusive organ, was also found in female rodents and humans . The prostate may be disrupted by EDCs, and studies with gerbils have demonstrated the injurious effects that environmental chemicals have on the development, and the maintenance of this gland throughout life . However, the effects of parabens in the prostate gland are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While in prostatic stroma, a reduction in proliferative activity was observed in both sexes. In females, such stromal decrease in cell proliferation may reflect the opposite effects of the two estrogen receptors (ER), ERα promotes cell proliferation (Ellem and Risbridger, ), while ERβ stimulates cell differentiation and has an anti‐proliferative role (Ellem and Risbridger, ; Rochel‐Maia et al, ; Perez et al, ). We have already observed that these two receptors present an increase in prostatic tissue staining in both males and females due to intrauterine estrogen exposure (Sanches et al, Unpublished data), which could partially justify the occurrence of opposing effects on prostate development in these cases.…”
Section: Discussionmentioning
confidence: 99%